Microfluidics in Sickle Cell Disease Research: State of the Art and a Perspective Beyond the Flow Problem - Aich, Anupam; Lamarre, Yann; Sacomani, Daniel Pereira; Kashima, Simone; Covas, Dimas Tadeu; de la Torre, Lucimara Gaziola (Frontiers in Molecular Biosciences, 2021)
Sickle cell disease (SCD) is the monogenic hemoglobinopathy where mutated sickle hemoglobin molecules polymerize to form long fibers under deoxygenated state and deform red blood cells (RBCs) into predominantly sickle form. Sickled RBCs stick to the vascular bed and obstruct blood flow in extreme conditions, leading to acute painful vaso-occlusion crises (VOCs) – the leading cause of mortality in SCD. Being a blood disorder of deformed RBCs, SCD manifests a wide-range of organ-specific clinical complications of life (in addition to chronic pain) such as stroke, acute chest syndrome and pulmonary hypertension in the lung, nephropathy, auto-splenectomy and splenomegaly, hand-foot syndrome, leg ulcer, stress erythropoiesis, osteonecrosis and osteoporosis. The physiological inception for VOC was initially thought to be only a fluid flow problem in microvascular space originated from increased viscosity due to aggregates of sickled RBCs; however, over the last three decades, multiple molecular and cellular mechanisms have been identified that aid the VOC in vivo. Activation of adhesion molecules in vascular endothelium, activation of adhesion molecules on RBC membranes, activated neutrophils and platelets, increased viscosity of the blood, and fluid physics driving sickled and deformed RBCs to the vascular wall (known as margination of flow) – all of these come together to orchestrate VOC. Microfluidic technology in sickle research was primarily adopted to benefit from mimicking the microvascular network to observe red blood cell flow under low oxygen conditions as models of VOC. However, over the last decade, microfluidics has evolved as a valuable tool to extract biophysical characteristics of sickle red cells, measure deformability of sickle red cells under simulated oxygen gradient and shear, drug testing, in vitro models of intercellular interaction on endothelialized or adhesion molecule-functionalized channels to understand adhesion in sickle microenvironment, characterizing biomechanics and microrheology, biomarker identification, and last but not least, for developing point-of-care diagnostic technologies for low resource setting. Several of these platforms have already demonstrated true potential to be translated from bench to bedside. Emerging microfluidics-based technologies for studying heterotypic cell-cell interactions, organ-on-chip application and drug dosage screening can be employed to sickle research field due to their wide-ranging advantages.